Wacana “Kerajaan Majapahit Bali”: Dinamika Puri Dalam Pusaran Politik Identitas Kontemporer - I. Putu Gede Suwitha (Jurnal Sejarah Citra Lekha, 2019)
This study discusses the transformation of the identity of the contemporary Balinese community in general and the dynamics of palaces (puri) in the political rotation in particular based on the discursive development of the “Bali Majapahit Kingdom”. This discourse can be observed from the local newspapers in Bali such as Bali Post, Tokoh, and so forth. The discourse of the “Bali Majapahit Kingdom” inspired by the Majapahit kingdom for the sake of image. The historical method was applied in this study. The data were analyzed descriptively-qualitatively using historical analysis. The result of the study shows that the discourse of the “Bali Majapahit Kingdom” has been inspired by a central figure named Aryawedakarna for his political interest. He has smartly used the Majapahit kingdom and the resurgence of Hinduism as the inspiration to establish the image as a royal figure. Actually, what he has done is the political identity and was successfully appointed a member of the Regional Representative Council [Dewan Perwakilan Daerah] with more or less 200,000 votes in the 2014 election.